Sof's doodles returning to my roots - Sofia Shamsunahar (MPH Group Publishing Sdn. Bhd., 2021)
Since she started a series of doodles to help her cope with a period in her life when the world felt like a very grey place, Sofia Shamsunaharhoned her unique method of storytelling and amassed a collection of tales on her Instagram page, @sofsdoodles. In this book are a selection of stories from that collection, featuring her thoughts on travel, forming human connections, self-love, and more -an invitation to open up, reach out and connect with others while accepting and staying true to who you are.